If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.6a + 11 = 67 Reorder the terms: 11 + 5.6a = 67 Solving 11 + 5.6a = 67 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 5.6a = 67 + -11 Combine like terms: 11 + -11 = 0 0 + 5.6a = 67 + -11 5.6a = 67 + -11 Combine like terms: 67 + -11 = 56 5.6a = 56 Divide each side by '5.6'. a = 10 Simplifying a = 10
| 6d-5-8d+2=1 | | -2(x-3)=5x+1 | | .5x+7=2x+10 | | .25x+.10y=4.75 | | x-.12=3.2 | | .25x+.10y=4.6 | | 3.9x-11.1=8.4 | | 21.75/2.25 | | -5x+14-2x= | | 3t-1=-5 | | 1/3d=70 | | -(2w-3)=21-5w+3 | | 3t-1=-4 | | 3(6+y)=4y-(16+y) | | 90-2x=76-x | | 2.5r=165 | | -23.4=-1.3y | | g(x)=10+20x | | -4=3-n/5 | | (2/3)-3 | | 2.25r=165 | | 7/20=/100 | | -1a+135=4a+105 | | 8x+4.17xy+17y+37y-14x+9.73= | | -14/2/7= | | 3z^2+6z=45 | | f(-6)=2x | | (4x+7)-2=29 | | 225(3.50+x)+150=2000 | | 3(-7)(-2)= | | f(n)=4n+3Findf(-5) | | 5y-4=12+14y |